The highly educated often have two children — childlessness and high numbers of children more commonly seen among low- and medium-educated persons - Jalovaara Marika; Miettinen Anneli (Turun yliopisto, 2022)
Lifetime childlessness has increased among men and women with lower (low or medium) education. Childlessness levels in Finland are high by international standards.
Simultaneously, high numbers of children are commonly seen among lower-educated men and women. Often, couples with lower level of education have three, four or more children. This is linked to an increase in ‘multipartner fertility’, or, having a child with more than one partner.
Highly educated men and women are more likely to have exactly two children. Both childlessness and a high number of children are less common among highly educated persons than among the lower educated, and this has not changed.